Resenha de: Sugar and Society in the Caribbean. An Economic History of Cuban Agriculture - Maria Theresa Schorer Petrone (Revista de História, 1966)
GUERRA Y SANCHEZ (Ramiro). — Sugar and Society in the Caribbean. — An Economic History of Cuban Agriculture; apêndice de José Antônio Guerra Debén e prefácio de Sidney W. Mintz; Caribbean Series. Yale University Press, New Haven and London, 1964.